Paving the Way: Contributions of Big Data to Apicomplexan and Kinetoplastid Research - Kent, Robyn S.; Briggs, Emma M.; Colon, Beatrice L.; Alvarez, Catalina; Silva Pereira, Sara; De Niz, Mariana (Frontiers in Cellular and Infection Microbiology, 2022)
In the age of big data an important question is how to ensure we make the most out of the resources we generate. In this review, we discuss the major methods used in Apicomplexan and Kinetoplastid research to produce big datasets and advance our understanding of Plasmodium, Toxoplasma, Cryptosporidium, Trypanosoma and Leishmania biology. We debate the benefits and limitations of the current technologies, and propose future advancements that may be key to improving our use of these techniques. Finally, we consider the difficulties the field faces when trying to make the most of the abundance of data that has already been, and will continue to be, generated.